Personalized design of ankle-foot prosthesis based on computer modeling of amputee locomotion - Gharini, Mohammad; Mohammadi Moghaddam, Majid; Farahmand, Farzam (Assistive technology, 2020)
This study proposes a computer modeling approach to find the optimal damping coefficients of the viscoelastic ankle-foot prostheses for each specific amputee. A two-dimensional locomotion model was developed for a transtibial amputee and personalized using his body measures and the reference gait pattern of an equivalent able-bodied subject. By employing the forward dynamic simulation, the amputee's locomotion was synthesized for different prosthetic settings to find the optimal damping coefficients, based on a kinematics and a total work cost function. Results indicated a good agreement between the model predictions and the experimental observations.